SOSIALISASI PENGELOLAAN SAMPAH DENGAN KONSEP 3R UNTUK MEMINIMALKAN SAMPAH RUMAH TANGGA - Wardani, Dila Dwiva Kusumah; Saputra, Jildan Mulya; Akmarti, Salma Rasda; Saffanah, Naja Silmi; Karwati, Lilis (Jurnal Pengabdian Masyarakat Indonesia, 2024)
The environment is something around humans that influences human life development. A good environment is one that is clean, healthy, and free from waste. The issue of waste in Indonesia is still a problem that has not been fully addressed. This also occurs in the Abdi Negara Housing Complex, where residents often dispose of waste improperly, leading to garbage being carried by rainwater and clogging the drains. The purpose of this socialization is to raise awareness among the community not to litter, especially into the drains, and it is hoped that the community can manage waste properly. The method used involves observation, followed by socialization using videos and practical waste management demonstrations explained in detail by the speaker, along with discussions with the residents of the Abdi Negara Housing Complex. The results of this socialization include increased awareness of the community in the Abdi Negara Housing Complex regarding environmental cleanliness, improved understanding of differentiating organic and inorganic waste, a growing desire to turn plastic waste into ecobricks, increased interest in weaving plastic waste into mats and turning it into a business opportunity.